1996
DOI: 10.1007/bf00189353
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for response to medical therapy in bacterial ulcerative keratitis

Abstract: In this population, ulcer size at the onset of antibacterial treatment and the use of certain ocular medications, specifically corticosteroids, were significant predictive factors for failure of medical therapy for BUK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In addition, ocular susceptibility to fungal infections is increased and fungal organisms have been shown to behave more aggressively after topical administration of corticosteroids (Pappa 1994;Brooks 1999). Other retrospective studies have identified topical corticosteroids as a predictor of poor outcome for infectious ulcerative keratitis in humans (Pappa 1994;Kim et al 1996;Wong et al 2003). These findings support the hypothesis that topical corticosteroids may allow increased bacterial colonisation, proliferation and the potential for increased virulence.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, ocular susceptibility to fungal infections is increased and fungal organisms have been shown to behave more aggressively after topical administration of corticosteroids (Pappa 1994;Brooks 1999). Other retrospective studies have identified topical corticosteroids as a predictor of poor outcome for infectious ulcerative keratitis in humans (Pappa 1994;Kim et al 1996;Wong et al 2003). These findings support the hypothesis that topical corticosteroids may allow increased bacterial colonisation, proliferation and the potential for increased virulence.…”
Section: Discussionsupporting
confidence: 60%
“…While epidemiologically useful, large studies have not shown a relation between antibiotic resistance and clinical outcomes [23,24]. This is not surprising as ophthalmic antibiotic preparations are applied topically at concentrations as high as three orders of magnitude greater than typical minimum inhibitory concentrations with resulting high corneal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…4,58 Retrospective studies of bacterial keratitis have not shown a correlation between susceptibility and the effects of initial antibacterial therapy. 30,[59][60][61] Interpreting these reports is limited by use of multiple antimicrobial agents and potential confounding by clinical severity. Relating antimicrobial susceptibility with outcome would help to establish evidence-based practice recommendations in ophthalmology.…”
Section: Commentmentioning
confidence: 99%